Teaching the number system to intermediate educable mentally retarded pupils through the use of variety of methods - Wright, Scott Mathews (1972)
Assuming that educable mentally retarded pupils have individual learning styles, and that concepts are developed by many and varied experiences, three main classifications of methods for introducing the number system to educable mentally retarded students are described: incidental learning methods, meaningful learning methods and drill methods. Methods within these classifications and activities developed according to the methods are presented, and suggestions are made for evaluation. The single method employed in the collection of information is library research.
Thesis (Master of Arts in Teaching - Special Education)--University of the Philippines, Diliman.
Keywords: Number theory; Mathematics -- Study and teaching (Elementary) -- Philippines; Children with mental disabilities -- Education (Elementary) -- Philippines; Special education -- Philippines